Membrane-cryogenic hybrid CO2 capture—A review - Chunfeng Song; Li Run; Qingling Liu; Shuai Deng; Hailong Li; Jianfeng Sun (Carbon Capture Science & Technology)
The membrane-cryogenic hybrid process is a promising CO2 capture process, which combines the advantages of membrane and cryogenic, such as high efficiency (up to 98 % CO2 captured) and low energy consumption (specific energy consumption around 1.7 MJ/kg CO2 avoided). Through pretreatment by membranes, CO2 concentration can be increased, which makes it possible to separate CO2 via phase change in the cryogenic unit. This work reviews the current status of the development of membrane-cryogenic hybrid processes. The synergy between membrane and cryogenic separation is summarized to identify the bottleneck of such processes and provide insights for process improvement. It was found that cold temperatures would be beneficial to reduce CO2 activation energy and then improve CO2 selectivity of membranes. To further improve the CO2 separation performance, the potential intensification methods of the membrane-cryogenic hybrid process including cold-membrane synthesis, process optimization via heat integration are discussed and envisioned.